Surviving New Kingdom Kings’ Coffins: Restoring the Art That Was - Kathlyn M. Cooney (Arts, 2025)
This article examines the material data preserved in king’s coffins used to bury and/or rebury five different kings, which represent the surviving material evidence we have of the art produced to manufacture divinized kingship during the New Kingdom: Seqenenre Taa, Kamose, Thutmose I/Panedjem I, Thutmose III, and Ramses II. All of them were removed from their original 17th and 18th Dynasty sepulchers, stripped of valuable materials, modified, and reused in later cache burials of the 20th, 21st, and 22nd Dynasties by 20th and 21st Dynasty High Priests of Amen, who used these recrafted coffins as a means of claiming their political and ideological legitimacy. Supported with detailed evidence of the five surviving king’s coffins as objects of social and political value and sometimes relying on the coffins recovered from Tutankhamun’s tomb for comparison, this article attempts to reconstruct some of the original material state of this art as a tool of power.